Molecular Insights: The Gut Microbiota's Impact on Colorectal Cancer - Samer Jarrar; Ghaleb Adwan (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Globally, colorectal cancer (CRC) ranks second in terms of cancer-related fatalities. Several lines of evidence point to the gut microbiota's role in increasing inflammation and tumour growth, despite the fact that CRC is believed to be the result of a genetic-environmental interaction. A person's gut microbiota is made up of around 40 trillion bacteria. Next-generation sequencing technologies and metagenomics have advanced the understanding of the ecology of gut microbes and have contributed to the connection between gut microbiota and colorectal cancer. Numerous investigations conducted on both human and animal models have highlighted the part that specific gut bacterialike Fusobacterium nucleatum, Bacteroides fragilis with enterotoxigenic properties, and Escherichia coli play critical role in the development and progression of colorectal cancer (CRC). New directions for the use of gut microbiota in CRC diagnosis, prevention, and therapy have been made possible by metagenomic research. The contribution of gut microbiota to colorectal cancer development and its possible therapeutic uses are outlined in this review paper